Pengaruh Pendapatan terhadap Konsumsi Rumah Tangga Petani di Desa Galang Manggarai Barat - any, sulfaidah; Vitra, Frumensia Avila; Sapinah, Sapinah (CV. Kalimasada Group, 2023)
Humans as individual and social beings have unlimited needs, both in quantity and type. To fulfill these various needs, individuals require income for consumption. This research aims to determine the influence of income on the consumption of farmers in Galang Village, Welak District, West Manggarai Regency. This study adopts a quantitative approach, emphasizing the analysis of numerical data. The population in this research is all farmers in Galang Village, Welak District, West Manggarai Regency, while the sampling technique uses purposive sampling with the criteria of farmers who own rice fields. The data analysis technique used is simple linear regression analysis. The research results show that the probability value is greater than alpha, namely 0.312 > 0.05, thus it can be concluded that income does not have a significant effect on the household consumption of farmers in Galang Village, Welak District, West Manggarai Regency. However, based on the regression equation, it indicates that an increase in income will result in an increase in consumption, although not significant.